PEMROGRAMAN BERORIENTASI OBYEK UNTUK PENGEMBANGAN SISTEM INFORMASI INVENTORY PADA PT. GIBOR - Indra Ava Dianta (UNIVERSITAS STEKOM, 2019)
Based on the survey conducted by the author at PT. Gibor, the author tries to develop an existing system in accordance with his knowledge, namely by changing the inventory system data processing program that still uses a single user system to a multiuser-based inventory data processing program with object-oriented programming language. Inventory information systems in a company play a very important role, if the goods sold consist of various types and with a fairly high turnover rate and one of the problems that often arises in a single user system is that data reports from warehouses often experience problems. error checking the amount of data items because the data items often experience changes so that the administration does not immediately know the changes. In solving these problems the author tries to collect data - data related to inventory, namely the data collection system of goods in purchase transactions and sales transactions. In designing this new system, the author also performs several stages, including making ERD and DFD diagrams to describe data storage and relationships between data. In designing the database the author determines the table to create the program and make the input and output design. These stages are carried out as a tool to create an object-oriented inventory system data processing program.